Dental Status and Oral Hygiene Practice among the Elderly People Attending at the Outpatient Department of BIRDEM Hospital, Dhaka (Bangladesh Journal of Dental Research & Education, 2013)
DOI: http://dx.doi.org/10.3329/bjdre.v2i1.15573 Bangladesh Journal of Dental Research & Education Vol.2(1) 2012: 17-21